A Novel Technique for Rapid-accurate 2D Hand Anthropometry - Fereshteh AKBARNEJAD; Reza OSQUEIZADEH; Hamid Reza MOKHTARINIA; Amir Salar JAFARPISHEH (Tehran University of Medical Sciences, 2017)
A Novel Technique for Rapid-accurate 2D Hand Anthropometry